The Role of Financial Performance in the Relationship between Sustainability Report and Company Value in Indonesia - Safitri, Dian Anggraeni; Setiawan, Pikar; Sedianingsih; Iswati, Sri (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to reveal the role of Financial Performance in the relationship between Sustainability Report and Value Company in Indonesia. The research population is a company going public on the Indonesia Stock Exchange that publishes a sustainability report. This study uses a quantitative approach. The sampling technique is purposive. The proxy value of the company is Q-Tobin. Proxy of Financial Performance is DER & ROE. Data processing uses Multiple Regression Analysis (MRA). The results showed that the relationship between Sustainability Report and Company Value was not significant without the role of DER and ROE. This means, significantly DER and ROE are true moderator variables. Although both variables are significant, the role of ROE is higher than that of DER. ROE is able to strengthen the relationship between Sustainability Report and Corporate Value of 82.70%, while DER strengthens the Sustainability Report relationship with the company value of 59.30%.